Daya Hambat Pasta Gigi yang Mengandung Ekstrak Biji Kopi Robusta (Coffea canephora) Terhadap Pertumbuhan Bakteri Aggregatibacter actinomycetemcomitans Secara In Vitro - Farahdila, Nihla Adinda; Pujiastuti, Peni; Sari, Desi Sandra (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2024)
Periodontitis is caused by bacteria in plaque, namely Aggregatibacter actinomycetemcomitans. Prevention of periodontal disease can be done by controlling plaque, namely brushing teeth using toothpaste to remove plaque and prevent plaque maturation. Alternative ingredients (herbs) that can be used to make toothpaste are robusta coffee beans which contain caffeine, flavonoids, trigonelin, and chlorogenic acid as antibacterial. The purpose of this study was to analyze the inhibition of toothpaste containing robusta coffee bean extract at concentrations of 6.25%, 12.5%, 25%, and 50% against the growth of A. actinomycetemcomitans. This type of research is experimental laboratory with posttest only control group design. This study was divided into 6 groups, namely positive control (Arabica coffee toothpaste), negative control (placebo paste), Robusta coffee bean extract toothpaste 6.25%, 12.5%, 25%, and 50%. Inhibition test using well diffusion method by making holes in the media. The diameter of the inhibition zone was measured using a caliper. The results showed that the control (-) group and the 6.25% group had no inhibitory power against the growth of A. actinomycetemcomitans. The robusta coffee bean extract toothpaste at concentrations of the 50% group (18.69 mm) had the greatest inhibition, but K (+) had greater inhibition than the 50% (22.89 mm) group. The conclusion of this study is that the robusta coffee bean extract toothpaste at concentrations of 12.5%, 25%, and 50% had inhibitory power against the growth of A. actinomycetemcomitans, but the greatest inhibitory power was at a concentration of 50%.